A solid electrolyte slurry, electrode slurry and application thereof

By using mixed solvents with multiple solvents proportioned to performance in all solid state batteries, the problem of unstable slurry performance caused by conventional low-polar solvents is solved, and higher electrochemical performance and a wider range of solvent binder selection are achieved.

CN119275337BActive Publication Date: 2025-04-25ENPOWER (PEKING) INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411803661.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Conventional low polarity solvents in all-solid state batteries lead to low slurry viscosity, poor solubility and unstable rheological performance, limiting the optional range of solid electrolyte slurry and electrode slurry.

Method used

A variety of different solvents are used to mix with a certain proportion according to their respective properties to form a mixed solvent to reduce the impact of the solvent on the performance of solid electrolytes and broaden the selection of solvent binder systems.

Benefits of technology

Through the complementary properties of multiple solvents, the electrochemical performance of all-solid state batteries is improved, the feasibility of industrial scale production is enhanced, and the coating status of electrode sheets and electrolyte membranes is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275337B_ABST
    Figure CN119275337B_ABST
Patent Text Reader

Abstract

The present invention provides a solid electrolyte slurry, electrode slurry and application, the solid electrolyte slurry includes a solid electrolyte, a binder and a mixed solvent; wherein the content of the solid electrolyte accounts for 80wt%-99wt% of the total solid material, the content of the binder accounts for 0.1wt%-5wt% of the total solid material, and the solid content of the solid electrolyte slurry is 20wt-80wt%; the mixed solvent includes N kinds of solvents, N≥2, the boiling point of the mixed solvent is 100℃-200℃, and the ionic conductivity decay of the solid electrolyte in the mixed solvent is ≤40%. The present invention overcomes the problems of low slurry viscosity, poor solubility and unstable rheological properties caused by conventional low-polarity solvents in solid-state batteries by using a variety of different solvents in a certain ratio according to their respective performances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries and relates to a solid electrolyte slurry, an electrode slurry and applications. Background Art

[0002] All-solid-state batteries are an important part of the future battery field and are considered to be the ultimate solution for batteries, but the current research on all-solid-state batteries is still in its early stages. Solid electrolytes are used in all-solid-state batteries to replace flammable liquid electrolytes, but because the intrinsic stability of solid electrolytes is poor, the mature solvent binder system in liquid batteries cannot be used. For this reason, in order to reduce the impact of solvents on solid electrolytes, all-solid-state batteries can only choose solvents with lower polarity, but low-polarity solvents usually have poor solubility for commonly used binders, making the binder insoluble or the viscosity of the glue insufficient. In addition, solvents with low polarity are usually highly volatile, making the solid content and rheological properties of the slurry unstable.

[0003] The slurry components of traditional liquid lithium-ion batteries only include active materials, conductive agents, binders, additives and other components that are not sensitive to the slurry system. Therefore, there are fewer issues to consider in the construction of the slurry system than for all-solid-state batteries. The slurry of all-solid-state batteries usually contains solid electrolytes that are sensitive to the slurry system. Therefore, before considering any method to optimize the slurry system, the stability of the slurry system to the solid electrolyte must be determined first, which limits the range of options for the slurry system.

[0004] Therefore, how to select solvents to overcome the adverse effects of low-polarity solvents on solid electrolyte slurry and electrode slurry is a problem that needs to be solved. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a solid electrolyte slurry, electrode slurry and application. The present invention overcomes the problems of low slurry viscosity, poor solubility and unstable rheological properties caused by the use of conventional low-polarity solvents in solid-state batteries by using a variety of different solvents in a certain ratio according to their respective properties. The complementary properties of a variety of solvents are conducive to broadening the optional range of solvent binders used in all-solid-state batteries, which is conducive to industrial-scale production, and the combination of solvents and binders with complementary properties can improve the electrochemical performance of all-solid-state batteries in many aspects.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] The present invention provides a solid electrolyte slurry, comprising a solid electrolyte, a binder and a mixed solvent; wherein the content of the solid electrolyte accounts for 80wt%-99wt% of the total solid material, the content of the binder accounts for 0.1wt%-5wt% of the total solid material, and the solid content of the solid electrolyte slurry is 20wt%-80wt%; the mixed solvent comprises N solvents, N≥2, the boiling point of the mixed solvent is 100°C-200°C, and the ionic conductivity attenuation of the solid electrolyte in the mixed solvent is ≤40%.

[0008] As a preferred embodiment of the present invention, N is 2-3; the boiling point of each solvent in the N solvents is 80°C-220°C; the attenuation range of the ionic conductivity of the solid electrolyte after being immersed in each solvent is 0-50%; the density of each solvent is 0.5g / cm 3 -1.5g / cm 3 ; The saturated vapor pressure range of each solvent at 25°C is 0.01kPa-100kPa; the dielectric constant range of each solvent at 25°C is 1-6; the viscosity range of each solvent at 20°C is 0.1mPa·S-1mPa·S.

[0009] As a preferred embodiment of the present invention, when N=2, the mixed solvent includes solvent M1 and solvent M2, the ion conductivity attenuation of the solid electrolyte in M1 is less than that in M2, and the volume ratio of M1 to M2 is (0.1-19):1;

[0010] Or, when N=3, the mixed solvent includes M1, M2 and M3, the ionic conductivity decay of the solid electrolyte in M1 is smaller than that in M2 and M3, the ionic conductivity decay of the solid electrolyte in M2 is smaller than that in M3, and the volume ratio of M1, M2 and M3 is (2-10):(0.1-10):(0.1-5).

[0011] As a preferred embodiment of the present invention, the mixed solvent is a combination of at least two of pentane, hexane, heptane, octane, decane, hexadecane, toluene, xylene, butyl butyrate, hexyl butyrate, benzyl acetate, isobutyl isobutyrate, anisole, dimethyl ether, butyl ether, cyclopentyl ether, petroleum ether or anhydrous ethanol.

[0012] As a preferred embodiment of the present invention, the particle size D of the solid electrolyte is 50 10nm-10μm.

[0013] The solid electrolyte includes a sulfide solid electrolyte (1-x) Li2S-xP2S5, a sulfide solid electrolyte Li2S-P2S5-MX, an oxide solid electrolyte A x B y O zOr halide solid electrolyte A x B y X z wherein 0<x<1, 0<y<1, 0<z<1, M is any one of Ge, Si or Al or a combination of at least two of them, X is any one of F, Cl, Br or I, A is any one of Li, Al, Ti, Zr or La or a combination of at least two of them, and B is any one of Li, Al, Ti, Zr or La or a combination of at least two of them.

[0014] As a preferred embodiment of the present invention, the binder includes any one of PVDF, PTFE, styrene-butadiene rubber, nitrile rubber, propylene rubber, butylene rubber, polyisoprene rubber, chloroprene rubber, styrene rubber, acrylic rubber, fluororubber or polyurethane, or a combination of at least two thereof.

[0015] In a second aspect, the present invention provides an electrode slurry, comprising a solid electrolyte, a binder, an active material, a conductive agent and a mixed solvent; wherein the content of the active material accounts for 40wt%-95wt% of the total solid material, the content of the solid electrolyte accounts for 4wt%-60wt% of the total solid material, the content of the binder accounts for 0.1wt%-5wt% of the total solid material, the content of the conductive agent accounts for 0.1wt%-5wt% of the total solid material, and the solid content of the electrode slurry is 20wt-80wt%; the mixed solvent includes N solvents, N≥2, the boiling point of the mixed solvent is 100℃-200℃, and the ionic conductivity decay of the solid electrolyte in the mixed solvent is ≤40%.

[0016] As a preferred embodiment of the present invention, N is 2-3; the boiling point of each solvent in the N solvents is 80°C-220°C; the attenuation range of the ionic conductivity of the solid electrolyte after being immersed in each solvent is 0-50%; the density of each solvent is 0.5g / cm 3 -1.5g / cm 3 ; The saturated vapor pressure range of each solvent at 25°C is 0.01kPa-100kPa; the dielectric constant range of each solvent at 25°C is 1-6; the viscosity range of each solvent at 20°C is 0.1mPa·S-1mPa·S.

[0017] When N=2, the mixed solvent includes solvent M1 and solvent M2, the ionic conductivity attenuation of the solid electrolyte in M1 is less than that in M2, and the volume ratio of M1 to M2 is (0.1-19):1;

[0018] Or, when N=3, the mixed solvent includes M1, M2 and M3, the ionic conductivity decay of the solid electrolyte in M1 is smaller than that in M2 and M3, the ionic conductivity decay of the solid electrolyte in M2 is smaller than that in M3, and the volume ratio of M1, M2 and M3 is (2-10):(0.1-10):(0.1-5).

[0019] As a preferred embodiment of the present invention, the active material is a positive electrode active material or a negative electrode active material.

[0020] The positive electrode active material includes any one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate or a lithium-rich manganese-based material or a combination of at least two thereof.

[0021] The negative electrode active material includes any one or a combination of at least two of graphite, hard carbon, pure silicon, silicon carbon, silicon oxygen, graphene, lithium titanate, alkali metal, alkaline earth metal or alloy negative electrode materials.

[0022] The conductive agent includes any one of super P, VGCF, acetylene black, Ketjen black, vapor-phase carbon fiber, carbon nanotube, nanocarbon fiber or graphene, or a combination of at least two thereof.

[0023] The particle size D of the solid electrolyte 50 10nm-10μm.

[0024] The solid electrolyte includes a sulfide solid electrolyte (1-x) Li2S-xP2S5, a sulfide solid electrolyte Li2S-P2S5-MX, an oxide solid electrolyte A x B y O z Or halide solid electrolyte A x B y X z wherein 0<x<1, 0<y<1, 0<z<1, M is any one of Ge, Si or Al or a combination of at least two of them, X is any one of F, Cl, Br or I, A is any one of Li, Al, Ti, Zr or La or a combination of at least two of them, and B is any one of Li, Al, Ti, Zr or La or a combination of at least two of them.

[0025] The binder includes any one of PVDF, PTFE, styrene-butadiene rubber, nitrile rubber, propylene rubber, butylene rubber, polyisoprene rubber, chloroprene rubber, styrene rubber, acrylic rubber, fluororubber or polyurethane, or a combination of at least two thereof.

[0026] The mixed solvent is a combination of at least two of pentane, hexane, heptane, octane, decane, hexadecane, toluene, xylene, butyl butyrate, hexyl butyrate, benzyl acetate, isobutyl isobutyrate, anisole, dimethyl ether, butyl ether, cyclopentyl ether, petroleum ether or anhydrous ethanol.

[0027] In a third aspect, the present invention provides a solid electrolyte membrane, which is prepared by using the aforementioned solid electrolyte slurry.

[0028] In a fourth aspect, the present invention provides an electrode plate, wherein the electrode plate is prepared using the aforementioned electrode slurry.

[0029] In a fifth aspect, the present invention provides an all-solid-state battery, which is prepared using the aforementioned solid electrolyte membrane and the aforementioned electrode plate.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The present invention can reduce the influence of solvents on the performance of solid electrolytes by using a variety of different solvents in a certain ratio according to their respective properties;

[0032] (2) The present invention uses a plurality of different solvents and mixes them in a certain ratio according to their respective properties. Thus, a solvent that is unstable to solid electrolytes but has other advantages can be used for the preparation of all-solid-state battery electrode slurry and solid electrolyte slurry. A solvent that is relatively stable to solid electrolytes but has some physical and chemical properties (such as boiling point, viscosity, density, etc.) that are not suitable for large-scale production can also be used for the preparation of all-solid-state battery electrode slurry and solid electrolyte slurry, so that the performances of the solvents complement each other.

[0033] (3) The present invention solves the problem of low solubility and viscosity of the binder in a solvent with high stability relative to the solid electrolyte by mixing a plurality of different solvents according to their respective properties in a certain ratio, which helps to broaden the selection of solvent-binder systems, thereby helping to improve the coating conditions of the electrode and the electrolyte membrane, and is beneficial to the performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The first cycle charge and discharge curve of the all-solid-state battery assembled in Comparative Example 1 of the present invention;

[0035] Figure 2 The first cycle charge and discharge curve of the all-solid-state battery assembled in Comparative Example 2 of the present invention;

[0036] Figure 3 The first cycle charge and discharge curve of the all-solid-state battery assembled in Example 1 of the present invention;

[0037] Figure 4The first cycle charge and discharge curve of the all-solid-state battery assembled in Example 2 of the present invention;

[0038] Figure 5 The first cycle charge and discharge curve of the all-solid-state battery assembled in Example 3 of the present invention;

[0039] Figure 6 The first cycle charge and discharge curve of the all-solid-state battery assembled in Example 4 of the present invention;

[0040] Figure 7 The first cycle charge and discharge curve of the all-solid-state battery assembled in Example 5 of the present invention;

[0041] Figure 8 The first cycle charge and discharge curve of the all-solid-state battery assembled in Example 6 of the present invention;

[0042] Fig. 9 The first cycle charge and discharge curve of the all-solid-state battery assembled in Example 7 of the present invention;

[0043] Fig.10 This is a SEM image of the electrode sheet prepared in Example 1 of the present invention;

[0044] Fig.11 This is a SEM image of the electrode sheet prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0045] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0046] The specific implementation mode of the present invention provides a solid electrolyte slurry, which includes a solid electrolyte, a binder and a mixed solvent; wherein the content of the solid electrolyte in the total solid material is 80wt%-99wt%, the content of the binder in the total solid material is 0.1wt%-5wt%, and the solid content of the solid electrolyte slurry is 20wt-80wt%; the mixed solvent includes N solvents, N≥2, the boiling point of the mixed solvent is 100℃-200℃, and the ionic conductivity attenuation of the solid electrolyte in the mixed solvent is ≤40%.

[0047] Among them, the content of solid electrolyte in all solid materials (solid electrolyte and binder) can be 80wt%, 85wt%, 90wt%, 95wt% or 98wt%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the content of binder in all solid materials (solid electrolyte and binder) can be 0.1wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the solid content of solid electrolyte slurry can be 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt% or 80wt%. wt% etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the value of N can be 2, 3, 4, 5, 6 or 7 or more values, and is not limited to the listed values; the boiling point of the mixed solvent can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable, preferably 120-200°C; the ionic conductivity attenuation of the solid electrolyte in the mixed solvent can be 40%, 35%, 30%, 25%, 20%, 10% or 5%, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable, preferably 0-30%.

[0048] In the present invention, N solvents refer to at least two solvents having different polarities or boiling points.

[0049] Ionic conductivity attenuation refers to the attenuation of ionic conductivity of solid electrolyte powder after immersion in mixed solvent for 24 hours. Attenuation = (ionic conductivity before immersion - ionic conductivity after immersion) ÷ ionic conductivity before immersion × 100%, which further indicates the polarity of the mixed solvent. An ionic conductivity attenuation greater than 40% indicates a high polarity, and vice versa.

[0050] The boiling point affects the volatility of the solvent.

[0051] The present invention mixes different types of solvents to make the mixed solvent meet the following conditions: boiling point of 100°C-200°C, ionic conductivity of solid electrolyte attenuation of ≤40% in the mixed solvent, density of 0.6g / cm 3 -1.1g / cm 3 , saturated vapor pressure at 25℃ 0.05kPa-90kPa, dielectric constant at 25℃ 1.5-5.5, viscosity at 20℃ 0.3mPa·S-0.85mPa·S.

[0052] As a preferred embodiment of the present invention, N is 2-3; the boiling point of each solvent in the N solvents is 80°C-220°C, such as 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C or 220°C, etc., but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the attenuation range of the ionic conductivity of the solid electrolyte after immersion in each solvent is 0-50%, such as 5%, 10%, 20%, 30%, 40% or 50%, etc., but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the density of each solvent is 0.5g / cm 3 -1.5g / cm 3 , for example 0.5g / cm 3 , 0.7g / cm 3 , 1g / cm 3 , 1.3g / cm 3 or 1.5g / cm 3 etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable; the saturated vapor pressure range at 25°C is 0.01kPa-100kPa, such as 0.01kPa, 1kPa, 5kPa, 10kPa, 30kPa, 50kPa, 70kPa or 100kPa, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable; the dielectric constant range of each solvent at 25°C is 1-6, such as 1, 2, 3, 4, 5 or 6, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable; the viscosity range of each solvent at 20°C is 0.1mPa·S-1mPa·S, such as 0.1mPa·S, 0.3mPa·S, 0.5mPa·S, 0.7mPa·S or 1mPa·S, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0053] As a preferred embodiment of the present invention, when N=2, the mixed solvent includes solvent M1 and solvent M2, the ionic conductivity attenuation of the solid electrolyte in M1 is less than that in M2, and the volume ratio of M1 to M2 is (0.1-19):1, such as 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1 or 20:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. Among them, the volume ratio is preferably 1:1.

[0054] In the present invention, when the mixed solvent includes two solvents, the volume ratio of solvents M1 and M2 needs to be controlled within a certain range. If the volume ratio of M1:M2 is too high, the boiling point, conductivity attenuation, density, saturated vapor pressure, dielectric constant and viscosity properties of the mixed solvent will be closer to M1, thereby offsetting the neutralizing effect of M2. For example, M1 usually has worse saturated vapor pressure and viscosity than M2. An excessively high M1 ratio will make the saturated vapor pressure and viscosity properties of the mixed solvent close to M1, while low saturated vapor pressure and viscosity will destroy the uniformity of the slurry and the dispersibility during coating.

[0055] Or, when N=3, the mixed solvent includes M1, M2 and M3, the ionic conductivity attenuation of the solid electrolyte in M1 is less than that in M2 and M3, respectively, the ionic conductivity attenuation of the solid electrolyte in M2 is less than that in M3, and the volume ratio of M1, M2 and M3 is (2-10):(0.1-10):(0.1-5), for example, 2:(0.1-1):(0.1-1), 4:(0.1-10):(0.1-5), 6:(0.1-10):(0.1-5), 8:(0.1-10):(0.1-5), 10:(0.1-10):(0.1-5), (2-10):0.5:(0.1-10): .1-5), (2-10):1:(0.1-5), (2-10):3:(0.1-5), (2-10):5:(0.1-5), (2-10):7:(0.1-5), (2-10):10:(0.1-5), (2-10):(0.1-10):0.5, (2-10):(0.1-10):1, (2-10):(0.1-10):2, (2-10):(0.1-10):3, (2-10):(0.1-10):4 or (2-10):(0.1-10):5, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. Among them, the volume ratio is preferably 2:1:1.

[0056] In the present invention, when the mixed solvent includes three solvents, the volume ratio of solvents M1, M2 and M3 needs to be controlled within a certain range. If the volume content of one of the solvents is too high, the boiling point, conductivity attenuation, density, saturated vapor pressure, dielectric constant and viscosity properties of the mixed solvent will be closer to those of the solvent with a higher content, thereby offsetting the neutralizing effect of M2 and M3. For example, M1 usually has a worse saturated vapor pressure and viscosity than M2. An excessively high proportion of M1 will make the saturated vapor pressure and viscosity properties of the mixed solvent close to those of M1, while low saturated vapor pressure and viscosity will destroy the uniformity of the slurry and the dispersibility during coating.

[0057] As a preferred embodiment of the present invention, the mixed solvent is a combination of at least two of pentane, hexane, heptane, octane, decane, hexadecane, toluene, xylene, butyl butyrate, hexyl butyrate, benzyl acetate, isobutyl isobutyrate, anisole, dimethyl ether, butyl ether, cyclopentyl ether, petroleum ether or anhydrous ethanol.

[0058] As a preferred embodiment of the present invention, the particle size D of the solid electrolyte is 50 It is 10nm-10μm, for example, 10nm, 50nm, 100nm, 300nm, 500nm, 700nm, 1μm, 3μm, 5μm, 7μm or 10μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] The solid electrolyte includes a sulfide solid electrolyte (1-x) Li2S-xP2S5, a sulfide solid electrolyte Li2S-P2S5-MX, an oxide solid electrolyte A x B y O z Or halide solid electrolyte A x B y X z wherein 0<x<1, 0<y<1, 0<z<1, M is any one of Ge, Si or Al or a combination of at least two of them, X is any one of F, Cl, Br or I, A is any one of Li, Al, Ti, Zr or La or a combination of at least two of them, and B is any one of Li, Al, Ti, Zr or La or a combination of at least two of them.

[0060] In the present invention, MX represents other dopants or adjusting components that may be added.

[0061] The specific sulfide solid state electrolysis can be Li 10 GeP2S 12 、Li7P3S 11 、Li3PS4、Li6PS5Cl、Li2S-P2S5 or Li 5.5 PS 4.5 Cl 1.5 etc.; Oxide solid electrolyte A x B y O z Can be Li7La3Zr2O 12 , LiTi2(PO4)3 or LaGaO3, etc.; Halide solid electrolyte A x B y X zIt can be Li3AlF6, Li3InCl6, Li3YCl6, Li3ErCl6, Li3YBr6, Li3ErBr6 or Li3InI6, etc.

[0062] The binder includes any one of PVDF, PTFE, styrene-butadiene rubber, nitrile rubber, propylene rubber, butylene rubber, polyisoprene rubber, chloroprene rubber, styrene rubber, acrylic rubber, fluororubber or polyurethane, or a combination of at least two thereof.

[0063] In the present invention, due to the sensitivity of solid electrolytes to the slurry system, the binders used in traditional liquid lithium-ion batteries are often not suitable for solid electrolytes. For example, the binder PVDF can usually only be dissolved in highly polar solvents, such as NMP, isobutyl isobutyrate, etc., and highly polar solvents will cause the ionic conductivity of the solid electrolyte to decay so severely that it cannot be used normally. Although weakly polar solvents such as toluene and xylene have little effect on the ionic conductivity of the solid electrolyte, their low solubility makes it impossible to dissolve PVDF glue. The present invention uses different types of solvents for mixing, thereby making glues such as PVDF soluble in mixed solvents and reducing the damage to the ionic conductivity of the solid electrolyte, so that the electrode slurry or solid electrolyte slurry and the obtained pole piece and electrolyte membrane can be used for all-solid-state batteries.

[0064] The specific embodiments of the present invention also provide a method for preparing the aforementioned solid electrolyte slurry, the preparation method comprising: mixing a solid electrolyte, a binder and a mixed solvent to obtain a solid electrolyte slurry; wherein the mixing comprises any one of mechanical ball milling, centrifugal homogenization, mechanical stirring or magnetic stirring or a combination of at least two; the mixing temperature is 15°C-150°C, for example, 15°C, 50°C, 100°C or 150°C, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the mixing speed is 100rpm-3000rpm, for example, 100 rpm, 500 rpm, 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm or 3000 rpm. rpm, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the mixing time is 5min-24h, for example 5min, 30min, 1h, 3h, 5h, 7h, 10h, 12h or 24h, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0065] The specific embodiment of the present invention also provides an electrode slurry, which includes a solid electrolyte, a binder, an active material, a conductive agent and a mixed solvent; wherein the content of the active material in the total solid material (referring to the solid electrolyte, the binder, the active material and the conductive agent) accounts for 40wt%-95wt%, such as 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 95wt%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the content of the solid electrolyte in the total solid material (referring to the solid electrolyte, the binder, the active material and the conductive agent) accounts for 4wt%-60wt%, such as 4wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt% or 60wt%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the content of the binder in the total solid material (referring to the solid electrolyte, the binder, the active material and the conductive agent) accounts for 0.1wt%-5wt%, such as 0.1wt%, 1wt%, 2 wt%, 3 wt%, 4 wt% or 5 wt%, etc., but are not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the content of the conductive agent in all solid materials (referring to solid electrolytes, binders, active materials and conductive agents) is 0.1wt%-5wt%, for example, 0.1wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, etc., but are not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the solid content of the electrode slurry is 20wt-80wt%, for example, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt% or 80wt%. wt%, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the mixed solvent comprises N solvents, N ≥ 2, and the boiling point of the mixed solvent is 100°C-200°C, such as 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable, preferably 120-200°C; the ionic conductivity of the solid electrolyte in the mixed solvent decays ≤40%, such as 40%, 35%, 30%, 25%, 20%, 10% or 5%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable, preferably 0-30%.

[0066] As a preferred embodiment of the present invention, N is 2-3; the boiling point of each solvent in the N solvents is 80°C-220°C, such as 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C or 220°C, etc., but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the attenuation range of the ionic conductivity of the solid electrolyte after immersion in each solvent is 0-50%, such as 5%, 10%, 20%, 30%, 40% or 50%, etc., but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the density of each solvent is 0.5g / cm 3 -1.5g / cm 3 , for example 0.5g / cm 3 , 0.7g / cm 3 , 1g / cm 3 , 1.3g / cm 3 or 1.5g / cm 3 etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable; the saturated vapor pressure range at 25°C is 0.01kPa-100kPa, such as 0.01kPa, 1kPa, 5kPa, 10kPa, 30kPa, 50kPa, 70kPa or 100kPa, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable; the dielectric constant range of each solvent at 25°C is 1-6, such as 1, 2, 3, 4, 5 or 6, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable; the viscosity range of each solvent at 20°C is 0.1mPa·S-1mPa·S, such as 0.1mPa·S, 0.3mPa·S, 0.5mPa·S, 0.7mPa·S or 1mPa·S, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0067] When N=2, the mixed solvent includes solvent M1 and solvent M2, the ionic conductivity attenuation of the solid electrolyte in M1 is less than that in M2, and the volume ratio of M1 to M2 is (0.1-19):1, such as 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1 or 19:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. Among them, the volume ratio is preferably 1:1.

[0068] Or, when N=3, the mixed solvent includes M1, M2 and M3, the ionic conductivity attenuation of the solid electrolyte in M1 is less than that in M2 and M3, respectively, the ionic conductivity attenuation of the solid electrolyte in M2 is less than that in M3, and the volume ratio of M1, M2 and M3 is (2-10):(0.1-10):(0.1-5), for example, 2:(0.1-1):(0.1-1), 4:(0.1-10):(0.1-5), 6:(0.1-10):(0.1-5), 8:(0.1-10):(0.1-5), 10:(0.1-10):(0.1-5), (2-10):0.5:(0.1-10): .1-5), (2-10):1:(0.1-5), (2-10):3:(0.1-5), (2-10):5:(0.1-5), (2-10):7:(0.1-5), (2-10):10:(0.1-5), (2-10):(0.1-10):0.5, (2-10):(0.1-10):1, (2-10):(0.1-10):2, (2-10):(0.1-10):3, (2-10):(0.1-10):4 or (2-10):(0.1-10):5, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. Among them, the volume ratio is preferably 2:1:1.

[0069] As a preferred embodiment of the present invention, the active material is a positive electrode active material or a negative electrode active material.

[0070] The positive electrode active material includes any one or a combination of at least two of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium cobalt oxide, lithium manganese oxide (including layered lithium manganese oxide and spinel lithium manganese oxide), lithium iron phosphate, lithium manganese iron phosphate or lithium-rich manganese-based materials.

[0071] The negative electrode active material includes any one or a combination of at least two of graphite, hard carbon, pure silicon, silicon carbon, silicon oxygen, graphene, lithium titanate, alkali metal, alkaline earth metal or alloy negative electrode materials.

[0072] The conductive agent includes any one of super P, VGCF, acetylene black, Ketjen black, vapor-phase carbon fiber, carbon nanotube, nanocarbon fiber or graphene, or a combination of at least two thereof.

[0073] The particle size D of the solid electrolyte 50 10nm-10μm.

[0074] The solid electrolyte includes a sulfide solid electrolyte (1-x) Li2S-xP2S5, a sulfide solid electrolyte Li2S-P2S5-MX, an oxide solid electrolyte A x By O z Or halide solid electrolyte A x B y X z wherein 0<x<1, 0<y<1, 0<z<1, M is any one of Ge, Si or Al or a combination of at least two of them, X is any one of F, Cl, Br or I, A is any one of Li, Al, Ti, Zr or La or a combination of at least two of them, and B is any one of Li, Al, Ti, Zr or La or a combination of at least two of them.

[0075] The binder includes any one of PVDF, PTFE, styrene-butadiene rubber, nitrile rubber, propylene rubber, butylene rubber, polyisoprene rubber, chloroprene rubber, styrene rubber, acrylic rubber, fluororubber or polyurethane, or a combination of at least two thereof.

[0076] The mixed solvent is a combination of at least two of pentane, hexane, heptane, octane, decane, hexadecane, toluene, xylene, butyl butyrate, hexyl butyrate, benzyl acetate, isobutyl isobutyrate, anisole, dimethyl ether, butyl ether, cyclopentyl ether, petroleum ether or anhydrous ethanol.

[0077] The specific embodiments of the present invention also provide a method for preparing the aforementioned electrode slurry, the preparation method comprising: mixing a solid electrolyte, a binder, an active material, a conductive agent and a mixed solvent to obtain an electrode slurry; wherein the mixing comprises any one of mechanical ball milling, centrifugal homogenization, mechanical stirring or magnetic stirring or a combination of at least two thereof; the mixing temperature is 15°C-150°C, for example, 15°C, 50°C, 100°C or 150°C, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the mixing speed is 100rpm-3000rpm, for example, 100 rpm, 500 rpm, 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm or 3000 rpm. rpm, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the mixing time is 5min-24h, for example 5min, 30min, 1h, 3h, 5h, 7h, 10h, 12h or 24h, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0078] The specific embodiments of the present invention also provide a solid electrolyte membrane, which is prepared by using the above-mentioned solid electrolyte slurry.

[0079] The specific embodiments of the present invention also provide an electrode plate, which is prepared by using the aforementioned electrode slurry.

[0080] The specific embodiments of the present invention also provide an all-solid-state battery, which is prepared using the aforementioned solid electrolyte membrane and the aforementioned electrode plate.

[0081] In the present invention, the preparation methods of the solid electrolyte membrane, electrode plate and all-solid-state battery are all conventional methods in the art.

[0082] The following are typical but non-limiting embodiments of the present invention: Embodiment 1:

[0083] This embodiment provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The solid electrolyte slurry is a sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 , binder NBR, solvent toluene and butyl butyrate, among which, sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 The mass ratio of toluene to binder NBR is 98:2, the volume ratio of toluene to butyl butyrate is 1:1, the boiling point of the mixed solvent is 120°C, and the solid content of the slurry is 60wt%.

[0084] The solid electrolyte membrane was prepared by using solid electrolyte slurry, and the method was as follows: the solid electrolyte slurry was mixed in a centrifugal homogenizer at a speed of 800 rpm for 10 minutes, the mixed slurry was coated on a stainless steel plate by a coater with a coating thickness of 200 μm, and the plate was placed in an oven at 80°C for drying, and the solid electrolyte membrane was obtained after peeling.

[0085] The electrode slurry includes a positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 , binder NBR, conductive agent VGCF, solvent toluene and butyl butyrate, the mass ratio of solid materials is 78:18:2:2, the volume ratio of toluene and butyl butyrate is 1:1, and the solid content of the slurry is 60wt%.

[0086] The electrode sheet was prepared by using the electrode slurry. The method was as follows: the electrode slurry was mixed in a centrifugal homogenizer at 800 rpm for 10 min, and then the mixed slurry was coated on a carbon-coated aluminum foil by a coating machine. The coating thickness was 80 μm, and the lithium ion positive electrode material loading was 10 mg / cm 2 , placed in an oven at 80°C for drying to obtain a pole piece. The SEM image of the pole piece is as follows: Fig.10 shown. Embodiment 2:

[0087] This embodiment provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the mixed solvent is xylene and butyl butyrate, the volume ratio of the two is 1:1, and the boiling point of the mixed solvent is 150°C.

[0088] The composition of the electrode slurry is the same as that of Example 1, except that the mixed solvent is xylene and butyl butyrate, the volume ratio of the two is 1:1, and the boiling point of the mixed solvent is 150°C.

[0089] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1. Embodiment 3:

[0090] This embodiment provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the mixed solvent is petroleum ether and butyl butyrate, the volume ratio of the two is 1:1, and the boiling point of the mixed solvent is 120°C.

[0091] The composition of the electrode slurry is the same as that of Example 1, except that the mixed solvent is petroleum ether and butyl butyrate, the volume ratio of the two is 1:1, and the boiling point of the mixed solvent is 120°C.

[0092] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1. Embodiment 4:

[0093] This embodiment provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the binder used is PVDF, the mixed solvent is petroleum ether and isobutyl isobutyrate, the volume ratio of the two is 1:1, and the boiling point of the mixed solvent is 130°C.

[0094] The composition of the electrode slurry is the same as that of Example 1, except that the binder used is PVDF, the mixed solvent is petroleum ether and isobutyl isobutyrate, the volume ratio of the two is 1:1, and the boiling point of the mixed solvent is 130°C.

[0095] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1. Embodiment 5:

[0096] This embodiment provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the binder used is PVDF, the mixed solvent is toluene and isobutyl isobutyrate, the volume ratio of the two is 1:1, and the boiling point of the mixed solvent is 140°C.

[0097] The composition of the electrode slurry is the same as that of Example 1, except that the mixed solvent is toluene and isobutyl isobutyrate, the volume ratio of the two is 1:1, and the boiling point of the mixed solvent is 140°C.

[0098] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1. Embodiment 6:

[0099] This embodiment provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the binder used is PVDF, the mixed solvent is xylene and isobutyl isobutyrate, the volume ratio of the two is 1:1, and the boiling point of the mixed solvent is 145°C.

[0100] The composition of the electrode slurry is the same as that of Example 1, except that the binder used is PVDF, the mixed solvent is xylene and isobutyl isobutyrate, the volume ratio of the two is 1:1, and the boiling point of the mixed solvent is 145°C.

[0101] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1. Embodiment 7:

[0102] This embodiment provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the binder used is PVDF, the mixed solvent is xylene, butyl butyrate and isobutyl isobutyrate, the volume ratio of the three is 2:1:1, and the boiling point of the mixed solvent is 150°C.

[0103] The composition of the electrode slurry is the same as that of Example 1, except that the mixed solvent is xylene, butyl butyrate and isobutyl isobutyrate, the volume ratio of the three is 2:1:1, and the boiling point of the mixed solvent is 150°C.

[0104] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1. Embodiment 8:

[0105] This embodiment provides a solid electrolyte slurry and electrode slurry, as well as a prepared solid electrolyte membrane and electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the solid electrolyte is Li3InCl6, the mixed solvent is heptane and benzyl acetate, the volume ratio of the two is 2:1, and the boiling point of the mixed solvent is 160°C.

[0106] The composition of the electrode slurry is the same as that of Example 1, except that the solid electrolyte is Li3InCl6, the mixed solvent is heptane and benzyl acetate, the volume ratio of the two is 2:1, and the boiling point of the mixed solvent is 160°C.

[0107] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1. Embodiment 9:

[0108] This embodiment provides a solid electrolyte slurry and electrode slurry, as well as a prepared solid electrolyte membrane and electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the solid electrolyte is Li3InCl6, the mixed solvent is octane and toluene, the volume ratio of the two is 1:2, and the boiling point of the mixed solvent is 120°C.

[0109] The composition of the electrode slurry is the same as that of Example 1, except that the solid electrolyte is Li3InCl6, the mixed solvent is octane and toluene, the volume ratio of the two is 1:2, and the boiling point of the mixed solvent is 120°C.

[0110] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1.

[0111] Comparative Example 1:

[0112] This comparative example provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the solvent is butyl butyrate.

[0113] The composition of the electrode slurry is the same as that of Example 1, except that the solvent is butyl butyrate.

[0114] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that of Example 1. The SEM image of the prepared electrode plate is as follows: Fig.11 shown.

[0115] Comparative Example 2:

[0116] This comparative example provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the binder used is PVDF and the solvent is isobutyl isobutyrate.

[0117] The composition of the electrode slurry is the same as that of Example 1, except that the binder used is PVDF and the solvent is isobutyl isobutyrate.

[0118] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1.

[0119] Comparative Example 3:

[0120] This comparative example provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the solvent is toluene.

[0121] The composition of the electrode slurry is the same as that of Example 1, except that the solvent is toluene.

[0122] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1.

[0123] Comparative Example 4:

[0124] This comparative example provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the solvent is xylene.

[0125] The composition of the electrode slurry is the same as that of Example 1, except that the solvent is xylene.

[0126] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1.

[0127] Comparative Example 5:

[0128] This comparative example provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the solvent is petroleum ether.

[0129] The composition of the electrode slurry is the same as that of Example 1, except that the solvent is petroleum ether.

[0130] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1.

[0131] Comparative Example 6:

[0132] This comparative example provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 8, except that the solvent is heptane and the solid electrolyte is Li3InCl6.

[0133] The composition of the electrode slurry is the same as that of Example 1, except that the solvent is heptane and the solid electrolyte is Li3InCl6.

[0134] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that of Example 8.

[0135] Comparative Example 7:

[0136] This comparative example provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the solvent is benzyl acetate and the solid electrolyte is Li3InCl6.

[0137] The composition of the electrode slurry is the same as that of Example 1, except that the solvent is benzyl acetate and the solid electrolyte is Li3InCl6.

[0138] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1.

[0139] Comparative Example 8:

[0140] This comparative example provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the solvent is octane and the solid electrolyte is Li3InCl6.

[0141] The composition of the electrode slurry is the same as that of Example 1, except that the solvent is octane and the solid electrolyte is Li3InCl6.

[0142] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1.

[0143] Comparative Example 9:

[0144] This comparative example provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the solvent is toluene and the solid electrolyte is Li3InCl6.

[0145] The composition of the electrode slurry is the same as that of Example 1, except that the solvent is toluene and the solid electrolyte is Li3InCl6.

[0146] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1.

[0147] Comparative Example 10:

[0148] This comparative example provides a solid electrolyte slurry and an electrode slurry, as well as a prepared solid electrolyte membrane and an electrode plate. The composition of the solid electrolyte slurry is the same as that of Example 1, except that the volume ratio of toluene to butyl butyrate is 100:1.

[0149] The composition of the electrode slurry is the same as that of Example 1, except that the volume ratio of toluene to butyl butyrate is 100:1.

[0150] The preparation method of the solid electrolyte membrane and the electrode plate is the same as that in Example 1.

[0151] Comparative Example 1: SEM image of the pole piece obtained ( Fig.10 ) and the SEM image of the electrode in Comparative Example 1 ( Fig.11 ), it can be seen that the components of the electrode in Example 1 are tightly combined, while the components of the electrode in Comparative Example 1 are looser, that is, Example 1 is easier to establish an effective ion conduction network. This may be because the solvent volatility of Comparative Example 1 is too high, which makes it difficult to maintain the uniformity of the electrode before and after during the coating process. This problem can be improved by applying a variety of solvents.

[0152] The ionic conductivity of the solid electrolyte powders used in Examples 1-9 and Comparative Examples 1-10 before immersion and after immersion for 24 hours, as well as the ionic conductivity decay and the ionic conductivity of the solid electrolyte membranes prepared are shown in Table 1.

[0153] Table 1: Ionic conductivity test results of Examples 1-9 and Comparative Examples 1-10

[0154]

[0155] As can be seen from Table 1, although the solvent of Comparative Example 1 has excellent performance in both the fluidity of the slurry and the volatility of the coating, it shows a large attenuation of the ionic conductivity of the solid electrolyte. This is mainly because the solvent of Comparative Example 1 has a strong polarity and is highly aggressive to the structure of the solid electrolyte. It can be seen from Examples 1-3 that after adding different second solvents (toluene, xylene and petroleum ether), the attack of the solvent on the solid electrolyte can be alleviated by adding a solvent with a lower polarity. Although the second solvents (toluene, xylene and petroleum ether) in Examples 1-3 have a lower polarity, they are difficult to use for homogenization and coating because the second solvent is highly volatile. This problem can be well solved by mixing with the first solvent. It can be seen from Comparative Examples 3-5 that using toluene, xylene or petroleum ether alone as solvents, the volatility of these three solvents is too strong, which will cause the slurry system to be unstable during the homogenization and coating process. The excessively fast solvent evaporation rate will cause the solid content of the slurry to change all the time, resulting in uneven coating, which in turn makes the components loose and reduces the first-cycle coulomb efficiency.

[0156] The binder PVDF used in Comparative Example 2 is soluble in the solvent isobutyl isobutyrate mentioned in Comparative Example 2, but the solvent has a strong polarity. It can be seen from the addition of the second solvent (petroleum ether, toluene and xylene) in Examples 4-6 that although the second solvent cannot dissolve the binder described in Comparative Example 2, its lower polarity neutralizes the aggressiveness of the first solvent. The effectiveness of this strategy is further demonstrated by the mixing of three solvents in Example 7. It shows that the mixing of multiple solvents can complement the effects of solvents to achieve better homogenous coating.

[0157] By comparing Examples 8-9 and Comparative Examples 6-9, it can be seen that after multiple solvents are mixed in Examples 8-9, the multi-solvent strategy achieves complementary performance of different solvents, and Examples 8-9 make up for the shortcomings of large attenuation of solvent ion conductivity or low boiling point in Comparative Example 6-9.

[0158] The pole pieces and electrolyte membranes prepared in Comparative Examples 1-2 and Examples 1-7 were used to prepare lithium-ion batteries, as follows:

[0159] The electrode and electrolyte membrane were cut into discs with a diameter of 12 mm. The cut electrode and electrolyte membrane were combined with a disc of lithium (negative electrode) with a diameter of 12 mm in the order described above. One side of the electrolyte layer was in contact with the electrode and the other side was in contact with the disc of lithium. The battery was assembled and its 0.1C charge and discharge capacity was tested. The voltage window was 2.8-4.2V. The charge and discharge curve of the first cycle was as follows: Figure 1-Figure 9 shown.

[0160] It can be seen that the performance of the battery in Examples 1-7 is significantly better than that in Comparative Examples 1-2. Figure 1 The first-cycle Coulomb efficiency of Comparative Example 1 is 76.5%. Figure 2 The first-cycle Coulomb efficiency of Comparative Example 2 is 61.36%. Figure 3 The first cycle coulombic efficiency of Example 1 is 87.43%. Figure 4 The first cycle coulombic efficiency of Example 2 is 88.25%. Figure 5 The first cycle coulombic efficiency of Example 3 is 83.03%. Figure 6 The first cycle coulombic efficiency of Example 4 is 82.56%. Figure 7 The first cycle coulombic efficiency of Example 5 is 81.48%. Figure 8 The first cycle coulombic efficiency of Example 6 is 80.29%. Fig. 9 The first cycle coulomb efficiency of Example 7 is 87.7%, and it can be seen that Examples 1-7 have higher first cycle coulomb efficiency than Comparative Examples 1-2. This is because the use of multiple solvents reduces the aggressiveness of solvent molecules to the solid electrolyte, improves the interface of the electrode, and has fewer interface side reactions, which is beneficial to the performance of the battery.

[0161] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A solid electrolyte slurry, characterized in that: The solid electrolyte slurry comprises a solid electrolyte, a binder and a mixed solvent; wherein the content of the solid electrolyte accounts for 80wt%-99wt% of the total solid material, the content of the binder accounts for 0.1wt%-5wt% of the total solid material, and the solid content of the solid electrolyte slurry is 20wt-80wt%; the mixed solvent comprises N solvents, N≥2, the boiling point of the mixed solvent is 100°C-200°C, and the ionic conductivity attenuation of the solid electrolyte in the mixed solvent is ≤40%; The mixed solvent is a combination of at least two of toluene, xylene, butyl butyrate, hexyl butyrate, benzyl acetate, isobutyl isobutyrate, anisole, dimethyl ether, butyl ether, cyclopentyl ether or petroleum ether; The binder comprises PVDF and / or nitrile rubber; The solid electrolyte includes a sulfide solid electrolyte (1-x) Li2S-xP2S5, a sulfide solid electrolyte Li2S-P2S5-MX, an oxide solid electrolyte A x B y O z Or halide solid electrolyte A x B y X z any one or a combination of at least two of, wherein 0<x<1, 0<y<1, 0<z<1, M is any one or a combination of at least two of Ge, Si or Al, X is any one of F, Cl, Br or I, A is any one or a combination of at least two of Li, Al, Ti, Zr or La, and B is any one or a combination of at least two of Li, Al, Ti, Zr or La; When N=2, the mixed solvent includes solvent M1 and solvent M2, the ionic conductivity attenuation of the solid electrolyte in M1 is less than that in M2, and the volume ratio of M1 to M2 is (1-10):1; Or, when N=3, the mixed solvent includes M1, M2 and M3, the ionic conductivity decay of the solid electrolyte in M1 is smaller than that in M2 and M3, the ionic conductivity decay of the solid electrolyte in M2 is smaller than that in M3, and the volume ratio of M1, M2 and M3 is (2-10):(0.1-10):(0.1-5).

2. The solid electrolyte slurry according to claim 1, characterized in that The N is 2-3; the density of each solvent is 0.5 g / cm 3 -1.5g / cm 3 ; The saturated vapor pressure range of each solvent at 25°C is 0.01kPa-100kPa; the dielectric constant range of each solvent at 25°C is 1-6; the viscosity range of each solvent at 20°C is 0.1mPa·S-1mPa·S.

3. The solid electrolyte slurry according to claim 1, characterized in that: The particle size D of the solid electrolyte 50 10nm-10μm.

4. An electrode slurry, characterized in that: The electrode slurry comprises a solid electrolyte, a binder, an active material, a conductive agent and a mixed solvent; wherein the content of the active material accounts for 40wt%-95wt% of the total solid material, the content of the solid electrolyte accounts for 4wt%-60wt% of the total solid material, the content of the binder accounts for 0.1wt%-5wt% of the total solid material, the content of the conductive agent accounts for 0.1wt%-5wt% of the total solid material, and the solid content of the electrode slurry is 20wt-80wt%; the mixed solvent comprises N solvents, N≥2, the boiling point of the mixed solvent is 100°C-200°C, and the ionic conductivity attenuation of the solid electrolyte in the mixed solvent is ≤40%; The mixed solvent is a combination of at least two of toluene, xylene, butyl butyrate, hexyl butyrate, benzyl acetate, isobutyl isobutyrate, anisole, dimethyl ether, butyl ether, cyclopentyl ether or petroleum ether; The binder comprises PVDF and / or nitrile rubber; The solid electrolyte includes a sulfide solid electrolyte (1-x) Li2S-xP2S5, a sulfide solid electrolyte Li2S-P2S5-MX, an oxide solid electrolyte A x B y O z Or halide solid electrolyte A x B y X z any one or a combination of at least two of, wherein 0<x<1, 0<y<1, 0<z<1, M is any one or a combination of at least two of Ge, Si or Al, X is any one of F, Cl, Br or I, A is any one or a combination of at least two of Li, Al, Ti, Zr or La, and B is any one or a combination of at least two of Li, Al, Ti, Zr or La; When N=2, the mixed solvent includes solvent M1 and solvent M2, the ionic conductivity attenuation of the solid electrolyte in M1 is less than that in M2, and the volume ratio of M1 to M2 is (1-10):1; Or, when N=3, the mixed solvent includes M1, M2 and M3, the ionic conductivity decay of the solid electrolyte in M1 is smaller than that in M2 and M3, the ionic conductivity decay of the solid electrolyte in M2 is smaller than that in M3, and the volume ratio of M1, M2 and M3 is (2-10):(0.1-10):(0.1-5).

5. The electrode slurry according to claim 4, characterized in that: The N is 2-3; the density of each solvent is 0.5 g / cm 3 -1.5g / cm 3 ; The saturated vapor pressure range of each solvent at 25°C is 0.01kPa-100kPa; the dielectric constant range of each solvent at 25°C is 1-6; the viscosity range of each solvent at 20°C is 0.1mPa·S-1mPa·S.

6. The electrode slurry according to claim 4, characterized in that: The active material is a positive electrode active material or a negative electrode active material; The positive electrode active material includes any one or a combination of at least two of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate or lithium-rich manganese-based materials; The negative electrode active material includes any one or a combination of at least two of graphite, hard carbon, pure silicon, silicon carbon, silicon oxygen, graphene, lithium titanate, alkali metal, alkaline earth metal or alloy negative electrode materials; The conductive agent includes any one or a combination of at least two of super P, VGCF, acetylene black, Ketjen black, vapor-phase carbon fiber, carbon nanotube, nanocarbon fiber or graphene; The particle size D of the solid electrolyte 50 10nm-10μm.

7. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane is prepared by using the solid electrolyte slurry as described in any one of claims 1 to 3.

8. An electrode plate, characterized in that: The electrode plate is prepared using the electrode slurry as described in any one of claims 4 to 6.

9. An all-solid-state battery, characterized in that: The all-solid-state battery is prepared using the solid electrolyte membrane as claimed in claim 7 and the electrode plate as claimed in claim 8.

Citation Information

Patent Citations

  • Sulfide electrolyte slurry, sulfide solid electrolyte and application thereof

    CN117525561A